Acceptance and implementation of evidence-based practices in delivery room resuscitation: A qualitative study - Cecelia L. Corson; Ingrid M. Nembhard; Christopher P. Bonafide; Elizabeth E. Foglia; Henry C. Lee; Sara C. Handley (SSM: Qualitative Research in Health)
Background: Variation persists in the implementation of evidence-based practices (EBPs) for delivery room resuscitation associated with high-quality care. To date, research has often studied leaders and rarely focused on the perspectives of delivery room resuscitation team members. We investigated team member perspectives on facilitators and barriers to accepting and implementing EBPs in delivery room resuscitation. Methods: This is a qualitative analysis of responses to open-ended questions in a twice-administered survey of delivery room resuscitation team members from a 16-hospital network. We conducted a two-phase content analysis, I) inductive conventional content analysis and II) deductive directed content analysis, to map response themes onto the three elements of the Promoting Action on Research Implementation in Health Services (PARIHS) framework – evidence, facilitation, and context. Results: There were 569 responses from 322 individuals representing all delivery room resuscitation team member roles. We identified five main themes that influence acceptance and implementation of EBPs: evidence, education, process characteristics, leadership, and change mindset. These themes aligned with the PARIHS framework elements of Evidence, Facilitation (occurring through education and process characteristics), and Context (determined by leadership and change mindset). We identified 12 sub-themes; 9 applied to both acceptance and implementation of EBPs, 1 applied only to acceptance of EBPs, and 2 applied only to implementation of EBPs. Conclusions: While many facilitators and barriers are consistent for both acceptance and implementation, some differ. To optimize EBPs in delivery room resuscitation, organizations may benefit from tailoring interventions to incorporate facilitators and address barriers that influence EBP acceptance and/or implementation.